In Vitro Antioxidant Activity of Extracts and Fractions from Common Bean (Phaseolus vulgaris L.) Pods and Leaves Using the DPPH Method: In Vitro Antioxidant Activity of Extracts and Fractions from Common Bean (Phaseolus vulgaris L.) Pods and Leaves Using the DPPH Method - Dita Meidinata; Novian Liu Wion (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2026)
Phaseolus vulgaris L. is a legume rich in nutrients and containing a variety of chemical constituents. Although its seeds have been extensively studied, comparative information regarding the antioxidant potential of the pod and leaf particularly in various solvent fractions has not yet been established. The objective of this study was to determine the in vitro antioxidant activity of ethanol extracts, n-hexane fractions, ethyl acetate fractions, and aqueous fractions of the pods and leaves of common bean (Phaseolus vulgaris L.) using UV-Visible spectrophotometry with the 1,1-dipheny l-2-picrylhydrazyl (DPPH) method. Phytochemical screening results indicated that the pods and leaves simplicia of the common bean contain flavonoids, polyphenols, saponins, monoterpenoids, sesquiterpenoids, and quinones. The n-hexane fraction of common bean leaves had an EC50 value of 7.16 µg/mL, and the aqueous fraction of common bean pod had an EC50 value of 10.24 µg/mL, each exhibited the strongest free radical scavenging activity compared to the other extracts and fractions. These values were determined using quercetin as a reference substance, which had a concentration of 0.6321 µg/mL. This indicates that common bean pods and leaves have potential as natural sources of antioxidant compounds. Therefore, further research is needed to isolate the compounds that act as antioxidants in common bean pod and leaf extracts, as well as to study the in vivo antioxidant activity of common beans.